[Image 19] - Smith, Captain Sir William [?ob. 1732] (My University, 1804)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of the Naval Signal Station at Fannat Point as seen looking towards Dunnaff, and Malin and Malin Head by Sir Wm Smith. This station designed, erected and built by him in 1804.
Keywords: Fannat Point; Dunnaff; Malin Head; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810